First report of Methylobacterium radiotolerans bacteraemia identified by MALDI-TOF mass spectrometry. (July 2019) - Cordovana, M.; Deni, A.; Kostrzewa, M.; Abdalla, M.; Ambretti, S.
Abstract: Methylobacterium radiotolerans is a fastidious, pink-pigmented, obligate aerobic Gram-negative bacillus commonly isolated from various environmental sources, and only occasionally from clinical samples, mostly in immunocompromised patients or associated with intravascular devices and haemodialysis. It grows poorly on commonly used culture media and its identification is time-consuming by conventional means. In this study, we present a case of M. radiotolerans bacteraemia in an individual affected by end-stage renal failure, identified by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The species identification was further confirmed by biochemical and molecular methods. The susceptibility to various antimicrobial agents is also presented and discussed.